2010
DOI: 10.1351/pac-con-09-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun materials for energy harvesting, conversion, and storage: A review

Abstract: Long-length nanofibers are able to form porous networks with high surface-areato-volume ratios, and decrease diffusion lengths. While there are numerous techniques to create nanostructures, electrospinning is the only technique that allows fabrication of nanofibers at long-length scales. These uniquely shaped fibers are applied to several energy-related devices. This review is an in-depth summary of the uses of electrospun fibers in dye-sensitized solar cells (DSSCs), batteries, capacitors, fuel cells, and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…In future work, the fabricated scaffolds (pristine and modified ones) will be further investigated as host matrix material for bone tissue regeneration. Finally, apart from bone tissue regeneration, PEI electrospun fibers could be utilized for other potential applications such as drug delivery [34], reinforcing of composite materials [35], filtration [36], and batteries [37].…”
Section: Introductionmentioning
confidence: 99%
“…In future work, the fabricated scaffolds (pristine and modified ones) will be further investigated as host matrix material for bone tissue regeneration. Finally, apart from bone tissue regeneration, PEI electrospun fibers could be utilized for other potential applications such as drug delivery [34], reinforcing of composite materials [35], filtration [36], and batteries [37].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the proton conductivity can be enhanced for more than 10 folds by means of the single electrospun polyelectrolytic nanofiber, as compared with its bulk membrane [17,18]. Therefore, Nafion, non-fluorinated polyelectrolytes and even inorganic proton conductors have been electrospun into nanofiber mats, and then the interfiber voids are filled with antiswelling polymers (either polyelectrolytic or uncharged) to prepare PEMs [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanofibers (CNFs) have enjoyed increasing use in a broad variety of nanotechnology applications, including materials and devices for the energy, environmental, biomedical, electronics, and structural sectors 1–7. Continuous carbon nanofibers are typically produced by carbonizing electrospun polymer‐based precursors 7, 8.…”
Section: Introductionmentioning
confidence: 99%